Hybrid Instantaneous Wave-Free Ratio–Fractional Flow Reserve versus Fractional Flow Reserve in the Real World - Shuttleworth, Kara; Smith, Kristina; Watt, Jonathan; Smith, Jamie A. L.; Leslie, Stephen J. (Frontiers in Cardiovascular Medicine, 2017)
Background The instantaneous wave-free ratio (iFR) is a novel method to assess the ischemic potential of coronary artery stenoses. Clinical trial data have shown that iFR has acceptable diagnostic agreement with fractional flow reserve (FFR), the reference standard for the functional assessment of coronary stenoses. This study compares iFR measurements with FFR measurements in a real world, single-center setting. Methods and results Instantaneous wave-free ratio and FFR were measured in 50 coronary artery lesions in 42 patients, with FFR ≤ 0.8 classified as functionally significant. An iFR-only technique, using a treatment cut-off value, iFR ≤ 0.89, provided a classification agreement of 84% with FFR ≤ 0.80. Use of a hybrid iFR–FFR technique, incorporating FFR measurement for lesions within the iFR gray zone of 0.86–0.93, would improve classification agreement with FFR to 94%, with diagnosis achieved without the need for hyperemia in 57% patients. Conclusion This study in a real-world setting demonstrated good classification agreement between iFR and FFR. Use of a hybrid iFR–FFR technique would achieve high diagnostic accuracy while minimizing adenosine use, compared with routine FFR.